Searching for Answers on a Clinical Information System - Safran, C. (Methods of Information in Medicine, 1995)
We examined observational data on the use of a clinical computing system in an effort to develop an empirical model of clinicians’ information needs. Clinicians turn to information systems most often to review the results of diagnostic studies. After that clinicians turn to information systems most often for communication. Bibliographic retrieval is the third most frequent reason for use, but is an order of magnitude less frequent than either results inquiry or electronic mail. Secondary retrieval of aggregate data from a clinical database is two orders of magnitude less common than primary retrieval. In a study at our hospital, clinicians gained access to an information resource during 16% of all general medical visits of patients with human immunodeficiency virus (HIV) infection while the patient was present. Insofar as our narrow focus on the primary care of HIV infection models the larger context of clinical medicine, clinicians are most often looking at information relating to therapeutics. Whatever knowledge structures are adopted, they must accommodate this observed need for therapeutic information.
Keywords: Clinical Computing Systems; Information Needs; Searching; Empirical Data Models; Electronic Medical Record; HIV Infection